Transformasi Kesiapan Atlet Korfball Kabupaten Bantul melalui Pendampingan Program Latihan Fisik Menuju PORPROV DIY 2024 - Sidik, Muhammad Asrul; Lestari, Bhekti; Eka Samudra, Fajar; Nurpratiwi, Resti; Alfan Triardhana, Yanuar; Rusdiawan, Afif; Kharis Fajar, Muhammad (Universitas Negeri Surabaya, 2025)
Abstract: The Regional Sports Week (PORDA) of the Special Region of Yogyakarta XVI in 2022 is the first event for the corpsball sport to be competed for the first time in Yogyakarta. The Bantul Regency team came out as the overall champion in the corpsball sport with gold medals in the two numbers contested. However, based on technique, the players from Bantul Regency are the most effective, but in terms of physical performance, the Bantul Regency Team is still not optimal. Based on the findings, it can be traced that it turns out that the coaching team does not have a written training program that is really programmed based on its periodization. The purpose of this activity is to help partners in preparing the team so that the target set by KONI Bantul Regency, namely the general champion at PORDA XVII DIY in 2025 can be achieved and the performance of the athletes will be optimal. The approach method carried out in this PKM program is in the form of physical test assistance and assistance in the preparation of training programs. The results of the physical test assistance and assistance in the preparation of this training program are expected to improve the physical condition of athletes. Keywords: 1; Training Program 2; Physical Test 3; Korfball 4; KONI Bantul Regency 5. PKSI Bantul Regency Abstrak: Pekan Olahraga Daerah (PORDA) Daerah Istimewa Yogyakarta XVI Tahun 2022 menjadi ajang perdana bagi cabang olahraga korfball pertama kali dipertandingkan di Yogyakarta. Tim Kabupaten Bantul keluar sebagai juara umum di cabor korfball dengan raihan medali emas pada dua nomor yang dipertandingkan. Namun berdasarkan teknik, para pemain dari Kabupaten Bantul paling efektif, namun secara performa fisik, Tim Kabupaten Bantul masih kurang optimal. Berdasarkan temuan, dapat ditelusuri bahwa ternyata tim kepelatihan tidak memiliki program latihan tertulis yang benar-benar terprogram berdasarkan periodesasinya. Tujuan dari kegiatan ini adalah untuk membantu mitra dalam mempersiapkan tim agar target yang dicanangkan oleh KONI Kabupaten Bantul, yakni juara umum pada PORDA XVII DIY Tahun 2025 dapat tercapai dan performa para atlet akan optimal. Metode pendekatan yang dilakukan dalam program PKM ini berupa pendampingan tes fisik dan pendampingan penyusunan program latihan. Hasil dari pendampingan tes fisik dan pendampingan penyusunan program latihan ini diharapkan dapat meningkatkan kondisi fisik atlet Kata Kunci: 1; Program Latihan 2; Tes Fisik 3; Korfball 4; KONI Kabupaten Bantul 5. PKSI Kabupaten Bantul